Antioxidant Activity Of Methanol And Ethanol/Water Extracts Of Tetrapleura Tetraptera And Parkia Biglobosa - MERCY BADU,; JOHN K. MENSAH,; NATHANIEL O. BOADI, (International Journal of Pharma and Bio Sciences, 2012)
Antioxidants present in natural sources help to scavenge free radicals and thus provide health benefits. This study reports in vitro radical scavenging and antioxidant capacity of crude methanol and ethanol-water extracts of the fruits of Tetrapleura tetraptera and Parkia biglobosa. Total phenolic contents in Tetrapleura tetraptera were 147.82±1.36 and 130.33±1.04 mg GAE/g dry weight while that of Parkia biglobosa were 128.32± 0.49 and 127.23±0.11 mg GAE/g dry weight respectively. The total antioxidant capacity of the extracts ranges from175.52±4.66 (methanol) to 172.87±2.15 mg/g (ethanol/water) for Tetrapleura tetraptera and from 160.44±2.26 (methanol) to 157.31±1.90 mg/g (ethanol/water) for Parkia biglobosa. The antioxidant activities of both fruits determined by the 2,2’-diphenyl-1-picrylhydrazyl radical (DPPH) and the reducing power (RPA) assays produced concentration-dependent values comparable to that of ascorbic acid control. The results of the study showed that fruits of Tetrapleura tetraptera and Parkia biglobosa have strong radical scavenging and reducing capacities.